The Existence and Significance of Muḥassināt Lafẓiyyah in Revealing the Beauty of Qur'anic Language - Ziyad Saevwa Rabbany; Suci Rizkiani (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The Qur'an is the greatest miracle with unparalleled linguistic beauty, which can be understood comprehensively through mastery of Balaghah Science, especially Badi' Science. This study aims to examine the existence and urgency of muhassinat lafdziyyah as an instrument to beautify the pronunciation of the holy verses of the Qur'an. The method used is qualitative with a library research approach, which takes data from primary sources such as the Book of Balaghah Al-Muyassaroh and other supporting secondary sources. The results of the discussion show that muhassinat lafdziyyah focuses on the beauty of phonetic aspects, sounds, letter harmony, and rhythm without sacrificing clarity of meaning. These forms of beautification are manifested through popular rhetorical devices such as Jinas (Jinas Tam and Jinas Naqish), Saja' (Mutharraf, Mutawazin, Mutawazi, and Murashsha), and Iqtibas (Ma'nawi, Tam, and with changes). This research confirms that the language style of the Qur'an is not merely an aesthetic ornament, but is very functional in conveying and emphasizing the deep theological meaning.